Paradise Blues Travels through American Environmental History - Mauch, Christof (The White Horse Press, 2024)
Paradise Blues is an unconventional history of the United States of America, an unusual travel guide that follows and renders visible the country's paths of nature, history and civilisation. Christof Mauch is a leading German historian who has spent many years in the US and in this book he attempts, from a European perspective, to grasp the diversity of American culture and the transformation of its environments, combining travel reporting with nature writing, personal observation and philosophical reflection. Mauch seeks the familiar in unfamiliar places and the curious in places that seem common and well-known. The journey begins in tiny Wiseman, Alaska and the final portrait is of Portland, Oregon, famously America's most sustainable city. In between, Mauch's wanderings in space and time, his serendipitous and planned encounters with places and people, bring to light the tension and ambivalence in most Americans' attitudes towards their often-perilous environment, the intertwining throughout history of valuation, conservation and destruction. Interactions between human beings and the environment have settled like sediment down the centuries and may be read in the present - in the form of landscapes and collective memory, in bodies of water and the earth's strata, tree rings and human cells. One of Mauch's dominant themes is that the grand hopes and bitter disappointments of the American paradise are not equally distributed - the blues is the voice of the dispossessed and disadvantaged; and here environmental injustice toward Black, Indigenous and other marginalised people is a recurring and haunting motif. This is a book of melancholia and hope - Mauch exposes the beauty, the imperilment, at times the wreckage, of the American environment. And he shows us that, more powerfully than abstract ideas, governmental edicts or technological forces, stories reveal the infinite discoveries to be made in humans' relationship to nature - in beautiful landscapes where danger lurks as well as in visions and behaviours that change the world and ecosystems. Above all, stories demonstrate that where we come from and where we are going are intimately connected and therefore nothing has to remain as it is. The stories told in Paradise Blues demonstrate that vulnerabilities and pressures are almost always political constructions and, for that reason, it must be possible to deconstruct them.